2016
DOI: 10.1371/journal.pone.0161758
|View full text |Cite
|
Sign up to set email alerts
|

Causal Attribution and Coping Maxims Differences between Immigrants and Non-Immigrants Suffering from Back Pain in Switzerland

Abstract: ObjectivesThis study aimed at investigating the relationship between causal attributions and coping maxims in people suffering from back pain. Further, it aimed at identifying in how far causal attributions and related coping maxims would defer between immigrants and non-immigrants in Switzerland.MethodsData for this study came from a larger survey study that was conducted among immigrant populations in the German- and Italian-speaking part of Switzerland. Included in the analyses were native Swiss participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Cultural backgrounds (non-native speakers) were also highly related to similar results. Interestingly, a study on causal attribution differences between immigrant and non-immigrant populations with back pain found that immigrants were more prone to consider physical activity as an attributed cause of back pain[ 69 ], which could encourage avoidance behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural backgrounds (non-native speakers) were also highly related to similar results. Interestingly, a study on causal attribution differences between immigrant and non-immigrant populations with back pain found that immigrants were more prone to consider physical activity as an attributed cause of back pain[ 69 ], which could encourage avoidance behavior.…”
Section: Discussionmentioning
confidence: 99%